The Application of Islamic Law in the Social Practices of Indonesia’s Multicultural Society - Hasmia Wahyunisa; Abdul Razak; Arifur Rahman; Fatema Khatun (Mahkota Science Publishers, 2026)
The law is no longer merely obeyed as a sacred text, but is reproduced as an arena of social dialectics steeped in interests, power and cultural compromise. This study aims to comprehensively analyse the process of negotiating Islamic law within the social practices of Indonesia’s multicultural society, and to identify the factors influencing these dynamics. This study employs a qualitative approach with an interpretative socio-legal design to understand Islamic law as a social practice shaped through the interaction between norms, interests, power relations and cultural contexts. The findings indicate that Islamic law can no longer be understood solely as an autonomous normative system, but rather as a social arena that is constantly undergoing construction and reconstruction through processes of meaning negotiation, legitimacy contestation, and compromise among stakeholders within a diverse society. This finding shifts the legal perspective from a textual orientation towards an understanding that positions law as a dynamic social process actively produced by various actors with diverse interests. The novelty of this study lies in its assertion that legal pluralism not only reflects the coexistence of various legal systems but also constitutes a space for the ongoing production of legitimacy. Consequently, the development of legal practice and policy must be directed towards a more dialogical, adaptive and inclusive approach, recognising the diversity of interpretations as an integral part of strengthening the legitimacy of the law within a multicultural society.